Panel with fire-resistant surface material on both sides
Patent Information
- Application Number
- JP2025149235
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2025-09-09
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 本発明によれば、耐火性、及び断熱性に優れた両面不燃面材付きパネルを提供することができる。
Smart Images

Figure 2026167391000003 
Figure 2026167391000004 
Figure 2026167391000005
Abstract
Description
[Technical Field]
[0001] The present invention relates to a panel with a double-sided non-combustible surface material having polyurethane foam as a core material. [Background technology]
[0002] In buildings, fire-resistant panels are sometimes provided in partition areas to improve fire resistance. As an example of a fire-resistant panel, a fire-resistant panel has been proposed that comprises a fibrous mat made by compression molding of rock wool fibers and metal plates bonded and integrated to both sides of the fibrous mat (see, for example, Patent Document 1).
[0003] Conventional fire-resistant panels made from rock wool fibers have poor thermal insulation properties. Therefore, in locations where thermal insulation is required, it is necessary to spray polyurethane foam, which has superior thermal insulation properties, onto the fire-resistant panels after installation to ensure adequate insulation. Furthermore, fire-resistant panels made from rock wool fibers are difficult to handle during installation and other processes due to the weight of the rock wool fibers. Therefore, for fire-resistant panels, the use of urethane foam or the like as a core material is being considered to improve thermal insulation performance and ease of handling (see, for example, Patent Document 2). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-123141 [Patent Document 2] Japanese Patent Publication No. 2021-088923 [Overview of the project] [Problems that the invention aims to solve]
[0005] However, while studies have been conducted to ensure fire resistance in polyurethane foam, taking into account the initial stages of a fire, there have been no polyurethane foams that have considered fire resistance in the higher temperature ranges of the peak of a fire. In other words, after the peak of a fire, polyurethane foam does not have sufficient fire resistance, and it is difficult to leave any residue after burning at high temperatures.
[0006] Therefore, the object of the present invention is to provide a panel with a double-sided non-combustible surface material that is excellent in fire resistance and heat insulation. [Means for solving the problem]
[0007] As a result of diligent research, the inventors have discovered that the above problems can be solved by incorporating a filler that meets an appropriate shape range into a urethane resin composition, which is the raw material for the polyurethane foam that forms the core material of a panel with a double-sided non-combustible surface material. Based on this discovery, the inventors have completed the present invention described below. In other words, the present invention provides the following [1] to [5].
[0008] [1] A panel with a double-sided non-combustible surface material having a core material which is a polyurethane foam formed from a urethane resin composition comprising a polyol compound, a polyisocyanate compound, a filler, a blowing agent, and a catalyst, wherein the parameters obtained by substituting the major diameter, medium diameter, minor diameter, and volume of the filler, obtained by image analysis of an image of the filler taken with an X-ray CT device, into the following formula (1) are greater than 0.10. (Longest diameter × Medium diameter ÷ Shortest diameter) ÷ Volume ... (1) [2] The panel with a double-sided non-combustible surface material according to [1], comprising the catalyst trimerizing catalyst. [3] The density of the core material formed from the urethane resin composition is 30 to 180 kg / m³ 3 A panel with a double-sided non-combustible surface material as described in [1] or [2]. [4] A panel with a double-sided non-combustible surface material according to any one of [1] to [3], wherein the thermal conductivity of the core material formed from the urethane resin composition is 0.035 W / (m·K) or less. [5] The panel with double-sided non-combustible face material according to any one of [1] to [4], wherein the core material formed from the urethane resin composition has a thickness of 50 to 300 mm. Effects of the Invention
[0009] According to the present invention, it is possible to provide a panel with double-sided non-combustible face material that is excellent in fire resistance and heat insulation properties. Brief Description of the Drawings
[0010] [Figure 1] This is a cross-sectional view of the panel with double-sided non-combustible face material according to one embodiment of the present invention. [Figure 2] This is a cross-sectional view of the panel with double-sided non-combustible face material according to one embodiment of the present invention. [Figure 3] This is a cross-sectional view of the panel with double-sided non-combustible face material according to one embodiment of the present invention. [Figure 4] This is a cross-sectional view of the panel with double-sided non-combustible face material according to one embodiment of the present invention. Modes for Carrying Out the Invention
[0011] Hereinafter, the present invention will be described with reference to embodiments. The panel with double-sided non-combustible face material of the present invention has a core material, and the core material is composed of a polyurethane foam formed from a urethane resin composition. The urethane resin composition used in the present invention includes a polyol compound, a polyisocyanate compound, a filler, a foaming agent, and a catalyst. Hereinafter, each component constituting the urethane resin composition will be described in detail.
[0012] [Filler] The filler is contained as a solid content in the urethane resin composition, and is a component that generally exists in a granular or powdery form in the urethane resin composition. In the present invention, the inclusion of the filler contributes to enhancing the residue retention property and the residue shape retention property of the polyurethane foam after combustion at high temperature, and can improve the fire resistance of the panel with double-sided non-combustible face material.
[0013] The filler is defined as a filler whose major axis, medium axis, minor axis, and volume, obtained by image analysis of images acquired with an X-ray CT (Computed Tomography) device, have parameters exceeding 0.10 when substituted into the following equation (1). (Longest diameter × Medium diameter ÷ Shortest diameter) ÷ Volume ... (1) Here, the X-ray CT scanner non-destructively scans the shape of the filler object in three dimensions (3D) and captures an image representing the shape of the filler. By analyzing the images captured by the X-ray CT scanner, the feature quantities of the filler region of each filler are obtained. The filler region refers to the area occupied by the filler itself, the major axis, medium axis, and minor axis of the feature quantities of the filler region refer to the major axis, medium axis, and minor axis of the smallest rectangular prism that encloses the filler, and the volume of the feature quantities of the filler region refers to the volume per filler. The actual size of the filler is calculated from the obtained feature quantities of the filler region. The average value of each is calculated by dividing the calculated actual size of the filler by the number of filler regions analyzed. Then, the average values of the major axis, medium axis, minor axis, and volume are substituted into equation (1) to obtain the above parameters.
[0014] In equation (1), the above parameter, i.e., (major diameter × medium diameter ÷ minor diameter), is an index indicating the shape of the filler. The larger the value, the more the shape deviates from a spherical shape, and the flatter it becomes. Therefore, the value of equation (1) increases as the flatterness increases and as the volume of each filler decreases. On the other hand, fillers remain when heated to high temperatures, for example, by fire, and act as components that maintain the shape of the residue. According to the inventors' research, it is estimated that the larger the value of equation (1), the bulkier the filler becomes, the easier it is for the fillers to remain due to their interaction with each other during combustion, and the easier it is for them to properly retain the residue. Therefore, if the value of equation (1) is 0.10 or less, it becomes difficult to impart excellent fire resistance to a panel with non-combustible surface material on both sides. From the above viewpoint, the above parameter is preferably 0.150 or more, more preferably 0.175 or more, and even more preferably 0.200 or more. The value of equation (1) is not particularly limited, but for example, it is 0.500 or less.
[0015] In addition, the average value of the equivalent spherical diameter of the filler is preferably 1 to 7 μm, more preferably 1 to 6 μm, and even more preferably 2 to 5 μm. When the average value of the equivalent spherical diameter of the filler is within the predetermined range, a relatively large amount can be contained in the polyol composition while moderately suppressing an increase in viscosity. The average value of the equivalent spherical diameter of the filler can be determined by calculating from the volume calculated by the above image analysis according to the following formula (2), and dividing the sum of the calculated equivalent spherical diameters by the number of filler regions analyzed. Equivalent spherical diameter (μm) = 2 × {Volume (μm 3 ) × 3 / 4 / pi} 1 / 3 (2)
[0016] The filler may be any component that is solid at normal temperature (23°C) and normal pressure (1 atm) and does not dissolve in the polyol composition. From the viewpoint of reducing the water absorption of the polyurethane foam, the filler preferably has no hygroscopicity and no deliquescence. Note that catalysts are not included in the filler.
[0017] Examples of the filler include diatomaceous earth, alumina, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, ferrites, calcium carbonate, magnesium carbonate, zinc carbonate, barium carbonate, dawsonite, hydrotalcite, calcium sulfate, barium sulfate, calcium silicate, talc, clay, mica, montmorillonite, bentonite, activated clay, sepiolite, imogolite, sericite, glass beads, silica balloons, aluminum nitride, boron nitride, silicon nitride, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, various magnetic powders, wollastonite, kaolin, graphite, barium sulfate, glass fibers, glass flakes, magnesium hydroxide, carbon fibers, aramid fibers, basalt fibers, and the like. Note that the graphite referred to herein is preferably other than expandable graphite.
[0018] Among the fillers listed above, mica, talc, wollastonite, kaolin, and graphite are preferred, with mica being the most preferred among them. Including mica makes it easier to improve the fire resistance of the polyurethane foam. Although the principle is not entirely clear, it is presumed that mica melts and binds together when heated, for example, to 800-1000°C, maintaining the shape of the residue, thereby providing excellent fire resistance. While there are no particular limitations on the type of mica, examples include muscovite, phlogopite, and margarite. These fillers may be used individually or in combination of two or more types.
[0019] The filler content is not particularly limited, but is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 50 parts by mass or more, and even more preferably 80 parts by mass or more, per 100 parts by mass of the polyol compound. Increasing the amount of filler makes it easier to impart high fire resistance. On the other hand, keeping the amount of filler below a certain level prevents the viscosity from becoming too high, making it easier to improve the productivity of the urethane resin composition. Since fire resistance improves as the filler content increases, there is no particular upper limit to the filler content, for example, 200 parts by mass.
[0020] [Polyol compounds] The polyol compound is not particularly limited, but examples include polyether polyols, polyester polyols, polylactone polyols, polycarbonate polyols, and polymer polyols. The polyol compound preferably contains at least one selected from polyester polyols and polyether polyols, and it is preferable to include polyester polyols from the viewpoint of improving the flame retardancy and fire resistance of the polyurethane foam. Furthermore, halogen-containing polyols and phosphorus-containing polyols may also be used from the viewpoint of improving flame retardancy and fire resistance. From the viewpoint of improving flame retardancy and fire resistance, the polyester polyol content is preferably 20 parts by mass or more, more preferably 50 parts by mass or more, even more preferably 80 parts by mass or more, and particularly preferably 100 parts by mass, per 100 parts by mass of the polyol compound.
[0021] The average hydroxyl value of the polyol compound is not particularly limited, but is preferably 100 to 700 mg KOH / g, more preferably 150 to 500 mg KOH / g, and even more preferably 180 to 400 mg KOH / g. The average hydroxyl value is the hydroxyl value of a single polyol compound if only one polyol compound is used, and the average value of hydroxyl groups according to the blending ratio of the two or more polyol compounds if two or more polyol compounds are used. For example, when using two types of polyol compounds, (d1) and (d2), if the hydroxyl value of polyol compound (d1) is X1 and the blending ratio is m1, and the hydroxyl value of polyol compound (d2) is X2 and the blending ratio is m2, the average hydroxyl value is expressed by the following formula. Note that the blending ratio is based on mass. Average hydroxyl value (mgKOH / g)=X1×(m1 / (m1+m2))+X2×(m2 / (m1+m2)) The hydroxyl value is measured in accordance with JIS K1557-1:2007.
[0022] The polyester polyol may be a polyester polyol having an aromatic ring or an aliphatic polyester polyol, but from the viewpoint of flame retardancy and fire resistance of the resulting polyurethane foam, it is preferable to use a polyester polyol having an aromatic ring. The polyester polyol having an aromatic ring is preferably a condensate of an aromatic dicarboxylic acid such as o-phthalic acid (phthalic acid), m-phthalic acid (isophthalic acid), p-phthalic acid (terephthalic acid), or naphthalenedicarboxylic acid with a glycol. In particular, from the viewpoint of improving the flame retardancy and fire resistance of the polyurethane foam, it is preferable that the polyester polyol includes a phthalic acid-based polyester polyol, which is a condensate of phthalic acid and glycol, and more preferably a p-phthalic acid-based polyester polyol, which is a condensate of p-phthalic acid and glycol. While the glycol is not particularly limited, it is preferable to use a low molecular weight aliphatic glycol known as a component of polyester polyols, such as ethylene glycol, propylene glycol, or diethylene glycol.
[0023] Examples of polyether polyols include polyoxyalkylene polyols obtained by ring-opening addition polymerization of alkylene oxide to an initiator having two or more active hydrogen atoms. Specific examples of initiators include aliphatic polyhydric alcohols such as glycols including ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexylene glycol, and cyclohexanedimethanol; triols such as trimethylolpropane and glycerin; tetrafunctional alcohols such as pentaerythritol; and highly functional alcohols such as sucrose and sorbitol. Aliphatic amines can also be used as initiators, including alkyleneamines such as ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, and neopentyldiamine; alkanolamines such as monoethanolamine and diethanolamine; and aromatic amines such as aniline, tolylenediamine, xylylenediamine, diphenylmethanediamine, and Mannich condensates. Of these, polyether polyols produced using an initiator having an aromatic ring are polyether polyols having an aromatic ring. For example, polyether polyols produced using an aromatic amine as an initiator are polyether polyols having an aromatic ring. Among polyether polyols having an aromatic ring, tolylenediamine-based polyether polyols and Mannich-based polyether polyols can be suitably used.
[0024] Tolylenediamine-based polyether polyols are tolylenediamine-based polyether polyols manufactured using tolylenediamine as an initiator. The above-mentioned Mannich-type polyether polyols are obtained using the Mannich reaction and are Mannich condensates having two or more hydroxyl groups in the molecule, or polyether polyols obtained by adding alkylene oxide to such Mannich condensates. More specifically, they are Mannich condensates obtained by the Mannich reaction of at least one of phenol and its alkyl-substituted derivatives, formaldehyde and alkanolamines, or polyether polyols obtained by ring-opening addition polymerization of these compounds with at least one of ethylene oxide and propylene oxide.
[0025] Examples of polylactone polyols include polypropiolactone glycol, polycaprolactone glycol, and polyvalerolactone glycol. Examples of polycarbonate polyols include polyols obtained by the de-alcoholization reaction of hydroxyl group-containing compounds such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, and nonanediol with ethylene carbonate, propylene carbonate, etc.
[0026] Examples of polymer polyols include polymers obtained by graft polymerization of ethylenically unsaturated compounds such as acrylonitrile, styrene, methyl acrylate, and methacrylate onto aromatic polyols, alicyclic polyols, aliphatic polyols, and polyester polyols, as well as polybutadiene polyols, or hydrogenated versions thereof.
[0027] The polyol compound content in the urethane resin composition of the present invention is preferably 8 to 60% by mass, more preferably 10 to 50% by mass, and even more preferably 15 to 40% by mass. When the polyol compound content is within the above range, a polyurethane foam can be formed appropriately.
[0028] [Polyisocyanate compounds] Examples of polyisocyanate compounds include aromatic polyisocyanates, alicyclic polyisocyanates, and aliphatic polyisocyanates. Examples of aromatic polyisocyanates include phenylene diisocyanate, tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanates such as 4,4'-diphenylmethane diisocyanate, dimethyl diphenylmethane diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, and polymethylene polyphenyl polyisocyanate (polymeric MDI).
[0029] Examples of alicyclic polyisocyanates include cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and dimethyldicyclohexylmethane diisocyanate. Examples of aliphatic polyisocyanates include methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate.
[0030] Among these, aromatic polyisocyanates are preferred from the viewpoint of reactivity and availability, and diphenylmethane diisocyanate, polymeric MDI, or mixtures thereof are more preferred. The polyisocyanate compound may be used alone or as a mixture of two or more.
[0031] The polyisocyanate compound content in the urethane resin composition should be adjusted so that the isocyanate index is greater than, for example, 100. When the isocyanate index is greater than 100, the amount of polyisocyanate compound relative to the polyol compound becomes excessive, making it easier for isocyanurate bonds to form from the polyisocyanate trimer. As a result, isocyanurate foam can be formed appropriately, making it easier to increase the residue retention rate and shape retention of the foam after high-temperature heating, and thus improving fire resistance. From the viewpoint of improving fire resistance by increasing the residue retention rate and shape retention after high-temperature heating, the isocyanate index is preferably 180 or higher, more preferably 250 or higher, even more preferably 300 or higher, and even more preferably 350 or higher. Furthermore, the isocyanate index is preferably 1000 or less, more preferably 800 or less, more preferably 600 or less, and even more preferably 550 or less. When the isocyanate index is below the above upper limit, performance commensurate with the manufacturing cost can be obtained.
[0032] The isocyanate index can be calculated using the following method. Isocyanate Index = Equivalents of polyisocyanate compound ÷ (Equivalents of polyol compound + Equivalents of water) × 100 Here, each equivalent number can be calculated as follows: • Equivalent weight of polyisocyanate compound = Amount of polyisocyanate compound used (g) × NCO content (mass%) / Molecular weight of NCO (moles) × 100 • Equivalent weight of polyol compound = OHV × Amount of polyol compound used (g) ÷ Molecular weight of KOH (millimoles) OHV is the hydroxyl value (mgKOH / g) of a polyol compound. • Equivalent amount of water = Amount of water used (g) / Molecular weight of water (moles) × Number of OH groups in water In the above formulas, the molecular weight of NCO is 42 moles, the molecular weight of KOH is 56,100 millimoles, the molecular weight of water is 18 moles, and the number of OH groups in water is 2.
[0033] [catalyst] (trimerization catalyst) The catalyst preferably includes at least a trimerizing catalyst. The trimerizing catalyst is a catalyst that reacts with the isocyanate groups contained in the polyisocyanate compound to trimerize them and promote the formation of an isocyanurate ring. By including the trimerizing catalyst, the urethane resin composition undergoes isocyanuration and can easily form an isocyanurate foam. Forming an isocyanurate foam makes it easier to improve fire resistance. Examples of trimerization catalysts include nitrogen-containing aromatic compounds, alkali metal carboxylates, tertiary ammonium salts, and quaternary ammonium salts. These may be used individually or in combination of two or more. Among these, it is preferable to use at least one of alkali metal carboxylates and quaternary ammonium salts as the trimerization catalyst, and it is also preferable to use both. Furthermore, among these, it is more preferable to use alkali metal carboxylates as the trimerization catalyst.
[0034] Examples of nitrogen-containing aromatic compounds used as trimerization catalysts include tris(dimethylaminomethyl)phenol, 2,4-bis(dimethylaminomethyl)phenol, and 2,4,6-tris(dialkylaminoalkyl)hexahydro-S-triazine. Examples of alkali metal carboxylate salts include potassium organic acids, preferably potassium octoates such as potassium 2-ethylhexanoate, potassium acetate, potassium propionate, potassium butanoate, potassium benzoate, and other potassium carboxylates having 2 to 8 carbon atoms.
[0035] Examples of tertiary ammonium salts include triethylammonium salt and triphenylammonium salt. Examples of quaternary ammonium salts include tetramethylammonium salt, tetraethylammonium salt, tetraphenylammonium salt, triethylmethylammonium salt, hydroxybutyltrimethylammonium salt, and hydroxypropyltrimethylammonium salt. Ammonium salts are, for example, ammonium salts of carboxylic acids. Examples of carboxylic acids in ammonium salts include saturated fatty acids having 1 to 10 carbon atoms, preferably 2 to 8 carbon atoms. Saturated fatty acids may have a linear hydrocarbon chain or a branched hydrocarbon chain, but branching is preferred. Specific examples of carboxylic acids include 2-ethylhexanoic acid, 2,2-dimethylpropanoic acid, acetic acid, and formic acid.
[0036] The trimerization catalyst content is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, even more preferably 1 to 10 parts by mass, and even more preferably 2 to 7 parts by mass, per 100 parts by mass of the polyol compound. When the trimerization catalyst content is within this range, the trimerization reaction can proceed appropriately at a rate commensurate with the amount of catalyst, and the isocyanurate ring can be formed appropriately. Therefore, it becomes easier to form a core material with good fire resistance.
[0037] (Resin-based catalyst) A resin catalyst may be used as the catalyst. A resin catalyst is a catalyst that promotes the reaction between a polyol compound and a polyisocyanate compound. By using a resin catalyst, the urethane reaction can be appropriately promoted at a good reaction rate, making it easier to form a polyurethane foam appropriately by, for example, the manufacturing method described later. Preferably, the catalyst contains a resin catalyst in addition to a trimerizing catalyst. By using both a trimerizing catalyst and a resin catalyst as catalysts, both the urethane reaction and the trimerizing reaction proceed appropriately, making it easier to form an isocyanurate foam appropriately by, for example, the manufacturing method described later.
[0038] Examples of resin-based catalysts include amine-based catalysts such as imidazole compounds and piperazine compounds, and metal-based catalysts. Examples of imidazole compounds include tertiary amines in which the secondary amine at position 1 of the imidazole ring is substituted with an alkyl group, alkenyl group, etc. Specifically, these include N-methylimidazole, 1,2-dimethylimidazole, 1-ethyl-2-methylimidazole, 1-methyl-2-ethylimidazole, 1,2-diethylimidazole, and 1-isobutyl-2-methylimidazole. Imidazole compounds in which the secondary amine in the imidazole ring is substituted with a cyanoethyl group are also examples. Furthermore, examples of piperazine compounds include tertiary amines such as N-methyl-N',N'-dimethylaminoethylpiperazine and trimethylaminoethylpiperazine. In addition to imidazole and piperazine compounds, amine catalysts include various tertiary amines such as pentamethyldiethylenetriamine, triethylamine, N-methylmorpholine bis(2-dimethylaminoethyl) ether, N,N,N',N”,N”-pentamethyldiethylenetriamine, N,N,N'-trimethylaminoethyl-ethanolamine, bis(2-dimethylaminoethyl) ether, N,N-dimethylcyclohexylamine, diazabicycloundecene, triethylenediamine, tetramethylhexamethylenediamine, and tripropylamine.
[0039] Examples of metal catalysts used as resinification catalysts include metal salts of lead, tin, bismuth, copper, zinc, cobalt, and nickel, with organic acid metal salts of lead, tin, bismuth, copper, zinc, cobalt, and nickel being preferred. More preferably, organic acid tin salts such as dibutyltin dilaurate, dioctyltin dilaurate, and dioctyltin versatate, and organic acid bismuth salts such as bismastrioctate and bismastrith(2-ethylhexanoate) are used, with organic acid bismuth salts being preferred among them. The resin catalyst may be used alone or in combination of two or more types. Preferably, the resin catalyst is at least one selected from amine-based catalysts and metal-based catalysts, with amine-based catalysts being more preferred, and imidazole compounds being even more preferred.
[0040] The resinification catalyst content in the urethane resin composition is preferably 0.1 to 10 parts by mass, more preferably 0.3 to 7.5 parts by mass, and even more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the polyol compound. When the resinification catalyst content is within this range, the reaction between the polyol compound and the polyisocyanate compound proceeds appropriately.
[0041] Furthermore, the total catalyst content in the urethane resin composition is not particularly limited, but is preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, and even more preferably 2 to 12 parts by mass, per 100 parts by mass of the polyol compound. When the total catalyst content is within this range, the reaction between the polyol compound and the polyisocyanate compound, as well as the trimerization reaction, proceeds smoothly.
[0042] [Foaming agent] The urethane resin composition contains a blowing agent. The inclusion of a blowing agent can promote the foaming of the urethane resin composition. Examples of blowing agents include organic physical blowing agents such as water, low-boiling hydrocarbons such as propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and cycloheptane; chlorinated aliphatic hydrocarbon compounds such as dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, and isopentyl chloride; ether compounds such as hydrofluoroolefins (hereinafter sometimes referred to as "HFO") and diisopropyl ether; or mixtures of these compounds; and inorganic physical blowing agents such as nitrogen gas, oxygen gas, argon gas, and carbon dioxide gas. The blowing agent preferably includes hydrofluoroolefin (HFO), which has high stability as a blowing agent, does not easily reduce catalytic activity, and also has a low environmental impact.
[0043] Suitable HFOs include fluoroalkenes having approximately 3 to 6 carbon atoms. The HFO may also be a hydrochlorofluoroolefin containing a chlorine atom, and therefore may also be a chlorofluoroalkene having approximately 3 to 6 carbon atoms. Examples of HFOs include trifluoropropene, tetrafluoropropene such as HFO-1234, pentafluoropropene such as HFO-1225, chlorodifluoropropene, chlorotrifluoropropene such as HFO-1233, and chlorotetrafluoropropene. More specifically, 3,3,3-trifluoropropene (HFO-1243zf), trans-1,3,3,3-tetrafluoropropene (HFO-1234ze(E)), cis-1,3,3,3-tetrafluoropropene (HFO-1234ze(Z)), 2,3,3,3-tetrafluoropropene (HFO-1234yf), 1,1,3,3-tetrafluoropropene, cis-1,3,3,3-tetrafluoropropene (HFO-1234ze(Z)), and trans-1,2,3,3,3-pene. Examples include tafluoropropene (HFO-1225ye(E)), cis-1,2,3,3,3-pentafluoropropene (HFO-1225ye(Z)), 1,1,3,3,3-pentafluoropropene (HFO-1225zc), 1,1,2,3,3-pentafluoropropene (HFO-1225yc), trans-1-chloro-3,3,3-trifluoropropene (HFO-1233zd(E)), and 1,1,1,4,4,4-hexafluorobuto-2-ene (HFO-1336mzz). Among these, HFO-1233zd(E) is preferred.
[0044] The amount of foaming agent in the urethane resin composition is not particularly limited, but is preferably 10 to 150 parts by mass, more preferably 15 to 120 parts by mass, and even more preferably 20 to 100 parts by mass, per 100 parts by mass of the polyol compound. If the foaming agent content is above the lower limit, foaming is promoted, resulting in good foamability, a reduction in the density of the polyurethane foam, and good heat insulation performance. If the foaming agent content is below the upper limit, excessive foaming can be suppressed.
[0045] The blowing agent may be used alone or in combination of two or more types. In the urethane resin composition of the present invention, it is preferable to use the above-mentioned HFO in combination with other blowing agents. For example, HFO may be used in combination with water, oxygen gas, or carbon dioxide gas, which have excellent handling properties. Water is particularly preferred from the viewpoint of adjusting the isocyanate index and from the viewpoint of ease of handling. The HFO content is preferably 10 to 150 parts by mass, more preferably 15 to 120 parts by mass, and even more preferably 20 to 100 parts by mass, per 100 parts by mass of the polyol compound. The water content is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and even more preferably 0.5 to 3 parts by mass, per 100 parts by mass of the polyol compound.
[0046] [Phosphate esters] The urethane resin composition may contain a phosphate ester. It is preferable to use a phosphate ester that is liquid at room temperature (23°C) and atmospheric pressure (1 atm). Using a phosphate ester allows it to function as a plasticizer, lowering the viscosity of the urethane resin composition and the polyol liquid described later, thus improving handling. Furthermore, the phosphate ester is also a liquid flame retardant, making it easier to improve the flame retardancy and fire resistance of the polyurethane foam.
[0047] As phosphate esters, monophosphate esters, condensed phosphate esters, etc., can be used. A monophosphate ester is a phosphate ester that has one phosphorus atom in its molecule. Examples of monophosphate esters include trialkyl phosphates such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, and tri(2-ethylhexyl) phosphate; halogen-containing phosphate esters such as tris(β-chloropropyl) phosphate; trialkoxy phosphates such as tributoxyethyl phosphate; aromatic ring-containing phosphate esters such as tricresyl phosphate, trixylenyl phosphate, tris(isopropylphenyl) phosphate, cresyldiphenyl phosphate, and diphenyl(2-ethylhexyl) phosphate; and acidic phosphate esters such as monoisodecyl phosphate and diisodecyl phosphate.
[0048] Examples of condensed phosphate esters include aromatic condensed phosphate esters such as trialkyl polyphosphates, resorcinol polyphenyl phosphates, bisphenol A polycresyl phosphates, and bisphenol A polyphenyl phosphates, as well as halogen-containing condensed phosphate esters such as polyoxyalkylene bisdichloroalkyl phosphates. Examples of commercially available condensed phosphate esters include "TMCPP," "CR-504L," "CR-733S," "CR-741," and "CR747" from Daihachi Chemical Industry Co., Ltd., and "ADEKA Stab PFR" and "FP-600" from ADEKA Corporation.
[0049] The phosphate esters may be used individually from the above-mentioned types, or two or more may be used in combination. Among these, monophosphate esters are preferred from the viewpoint of easily lowering viscosity and improving the flame retardancy of the polyurethane foam, and halogen-containing phosphate esters such as tris(β-chloropropyl)phosphate are more preferred. The phosphate ester content in the urethane resin composition is, for example, 5 to 150 parts by mass, preferably 15 to 130 parts by mass, more preferably 20 to 120 parts by mass, and even more preferably 40 to 110 parts by mass, per 100 parts by mass of the polyol compound.
[0050] [Foam stabilizer] The urethane resin composition may contain a foam stabilizer. Including a foam stabilizer improves the foaming properties of the polyurethane foam, and for example, it can appropriately promote foaming in the manufacturing method described later. Examples of foam stabilizers include surfactants, more specifically, polyoxyalkylene foam stabilizers such as polyoxyalkylene alkyl ethers, and silicone foam stabilizers such as organopolysiloxanes. The foam stabilizer used in the present invention is not particularly limited, but silicone foam stabilizers are preferred from the viewpoint of foaming properties. The foam stabilizer may be used alone or in combination of two or more types.
[0051] The foam stabilizer content in the urethane resin composition is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and even more preferably 0.5 to 3 parts by mass, per 100 parts by mass of the polyol compound. When the foam stabilizer content is above the lower limit, the urethane resin composition becomes easier to foam, making it possible to obtain a homogeneous polyurethane foam. Furthermore, when the foam stabilizer content is below the upper limit, the balance between manufacturing cost and the obtained effect is optimized.
[0052] [Other ingredients] The urethane resin composition may also contain flame retardants other than the fillers mentioned above. Furthermore, the urethane resin composition may, in addition to the above, contain, as necessary and within the limits that do not impair the objectives of the present invention, one or more agents selected from phenolic, amine, and sulfur-based antioxidants, heat stabilizers, metal damage inhibitors (metal deactivators), antistatic agents, crosslinking agents, lubricants, softeners, dispersants, pigments, dyes, tackifiers, etc.
[0053] The urethane resin composition may be a one-component type, or it may be used by dividing it into two or more parts and mixing them. When dividing it into two or more parts, it is preferable to divide it into at least a polyol liquid containing a polyol compound and an isocyanate liquid containing a polyisocyanate compound. The urethane resin composition is preferably a two-component type. In the two-component type, it is preferable to consist of a polyol liquid and an isocyanate liquid. In a two-component system, the various components such as the filler and catalyst may be included in either the polyol liquid or the isocyanate liquid, but from the viewpoint of storage stability, it is preferable to include them in the polyol liquid. Furthermore, it is preferable to include components other than the filler and catalyst, such as foaming agents, phosphate esters, foam stabilizers, and other components, in the polyol liquid.
[0054] A urethane resin composition can be manufactured by mixing the various components that make up the urethane resin composition. In the case of a two-component type, it can be obtained by mixing a polyol liquid and an isocyanate liquid. If each of these liquids contains two or more components, it can be obtained by mixing the components that make up each liquid.
[0055] <Polyurethane foam> The polyurethane foam constituting the core material of the present invention can be formed by foaming and curing the above-described urethane resin composition. The method for foaming and curing the urethane resin composition can be a known method. For example, in the case of a two-component type, the polyurethane foam can be obtained by mixing the polyol liquid agent and the isocyanate liquid agent prepared in advance as described above, and then foaming and curing the resulting urethane resin composition. The polyurethane foam may be any rigid urethane foam, but it is preferable that it be an isocyanurate foam isocyanurated with an excess amount of polyisocyanate compound as described above.
[0056] Polyurethane foam (core material) has a density of 30-200 kg / m³ 3 Preferably, it is 35-190 kg / m 3 It is more preferable that the load is 40-180 kg / m³.3 It is even more preferable that the polyurethane foam has a density of 30-180 kg / m³. 3 It is also preferable that the polyurethane foam has a density above a certain level, which makes it easier to improve its fire resistance. Furthermore, by keeping the density of polyurethane foam below a certain level, its thermal conductivity decreases, making it easier to improve its insulation properties. In addition, since polyurethane foam can be made lighter, it becomes easier to handle during construction, for example. Note that the density refers to the overall density, and the details of its measurement method are described in the examples.
[0057] The polyurethane foam (core material) should have a volume retention rate of, for example, 20% or higher, preferably 50%, and more preferably 80%, after being heated from 600°C to 800°C and maintained at 800°C for 14 minutes. By maintaining a volume retention rate of above a certain level as described above, the polyurethane foam of the present invention is more likely to exhibit good fire resistance in the event of a fire. The volume retention rate should be 100% or less, but practically it may be 97% or less. The volume retention rate can be measured by the method described in the examples below.
[0058] The polyurethane foam (core material) preferably has a thermal conductivity of 0.035 W / (m·K) or less. Having a thermal conductivity of less than or equal to the above upper limit of the polyurethane foam provides good heat insulation. From the viewpoint of heat insulation, the thermal conductivity is more preferably 0.03 W / (m·K) or less, even more preferably 0.028 W / (m·K) or less, and even more preferably 0.024 W / (m·K) or less. The thermal conductivity can be measured by the method described in the examples below.
[0059] The polyurethane foam preferably has a flyability of 65% or less, more preferably 60% or less, and even more preferably 50% or less. A flyability below a certain level makes it easier to achieve good fire resistance. Flyability can be obtained, for example, by the measurement method shown below. (Measurement method) Flyability is measured in accordance with ASTM-C-421-61. Specifically, twelve pieces of polyurethane foam cut to 25 x 25 x 25 mm are prepared, their mass is measured, and they are placed in a measuring instrument along with 24 pieces of wood (19 ± 0.8 mm). After 600 rotations, the resulting powder is removed, and the mass after the test is measured. The decrease in mass from the original mass is calculated as a percentage, and this calculated value is defined as the flyability.
[0060] The polyurethane foam preferably has a closed-cell ratio of 75% or more, more preferably 80% or more, and even more preferably 85% or more. Maintaining a closed-cell ratio above a certain level makes it easier to maintain good thermal insulation properties of the polyurethane foam. The closed-cell ratio is a value measured according to ASTM D2856.
[0061] <Panel with double-sided fire-resistant surface material> The double-sided fire-resistant panel of the present invention has a core material made of polyurethane foam formed from the above-mentioned urethane resin composition. As shown in Figure 1, the double-sided fire-resistant panel 10 has a pair of opposing panels 20, 21 and a core material 11 sandwiched between them. The thickness of the core material 11 is preferably 50 to 300 mm, more preferably 60 to 290 mm, and even more preferably 70 to 280 mm. Having the core material 11 within the above thickness range provides high fire resistance and heat insulation, while also allowing for weight reduction.
[0062] The facing materials 20 and 21 are non-combustible facing materials. Examples of non-combustible facing materials include calcium silicate board, gypsum board, FRP, and metal sheets, with metal sheets being preferred. Therefore, it is preferable that the facing materials 20 and 21 are metal facing materials. By using metal sheets as facing materials, good fire resistance can be achieved. There are no particular limitations on the metal facing material, but various steel sheets such as galvanized steel sheets, galvalume steel sheets (registered trademark), stainless steel sheets, and aluminum steel sheets can be used. In other words, it is more preferable that the panel 10 with non-combustible facing materials on both sides is a panel with steel sheets on both sides. The facing materials 20 and 21 are bonded to the front and back surfaces of the core material 11, respectively. The facing materials 20 and 21 may be directly bonded to the core material 11, but there may also be layers other than the core material and non-combustible facing materials (hereinafter also referred to as any layer), such as paper sheets, aluminum plates, aluminum kraft sheets, polyethylene laminate sheets, or cloth laminate sheets, between the facing materials 20 and 21 and the core material 11.
[0063] Furthermore, to further improve fire resistance, an inorganic core material may be combined with the core material 11. Examples of inorganic core materials include core materials containing mineral fibers such as rock wool, glass wool, glass filaments, special-purpose glass microfibers, ceramic wool, alkali earth silicate wool (AES), refractory ceramic fiber (RCF), alumina fibers, potassium titanate whiskers, silicon carbide whiskers, calcium silicate boards, and ALC panels. As shown in Figure 2, the inorganic core material 12 may be laminated on only one side of the core material 11. Note that the configuration when the inorganic core material 12 is laminated on only one side of the core material 11 is not limited to the configuration shown in Figure 2. For example, the inorganic core material 12 may be positioned on the upper side and the core material 11 on the lower side, or at least two layers of either the core material 11 or the inorganic core material 12 may be laminated.
[0064] Furthermore, as shown in Figure 3, inorganic core materials 12 and 14 may be laminated on both sides of the core material 11, resulting in a configuration with three or more layers in total. In this case, a three-layer configuration is possible as shown in Figure 3, but the configuration is not limited to that shown in Figure 3. For example, at least two or more layers of inorganic core materials 12 and 14 may be laminated onto the core material 11. The thicknesses of the inorganic core materials 12 and 14 laminated on both sides of the core material 11 may be symmetrical on both sides of the core material 11. For example, they may be laminated in the order of 50mm thick inorganic core material 12 / 50mm thick core material 11 / 50mm thick inorganic core material 14. However, they do not necessarily have to be symmetrical. For example, they may be laminated in the order of 20mm thick inorganic core material 11 / 50mm thick core material 12 / 80mm thick inorganic core material 14.
[0065] Furthermore, as shown in Figure 4, the core material may be configured to have three or more layers in total, including the inorganic core material 11 and 13, by laminating core materials 11 and 13 on both sides of the inorganic core material 12. In this case, it may be a three-layer configuration as shown in Figure 4, but it is not limited to the configuration shown in Figure 4. For example, at least two or more layers of any of the core materials 11 and 13 may be laminated on the inorganic core material 12. Furthermore, the thickness of the core materials 11 and 13 laminated on both sides of the inorganic core material 12 may be symmetrical or asymmetrical on both sides of the inorganic core material 12, similar to the inorganic core materials 12 and 14 described above.
[0066] The thickness of each facing material 20, 21 is preferably 0.1 to 5 mm, more preferably 0.2 to 3 mm, and even more preferably 0.3 to 1 mm. A thickness of facing materials 20, 21 greater than or equal to the lower limit provides high fire resistance. Furthermore, a thickness of facing materials 20, 21 less than or equal to the upper limit allows for weight reduction of the double-sided non-combustible facing panel 10. The facing materials 20 and 21 may be flat, plate-shaped members, or, if a surface material is provided to cover the sides of the core material 11 (described later), the facing materials 20 and 21 may be U-shaped or L-shaped members, in which case a portion of the U-shaped or L-shaped member may constitute the surface material that covers the sides.
[0067] In a panel with double-sided non-combustible surface material, the sides (other than the front and back surfaces) of the core material 11 covered by the surface material 20, 21 may also be appropriately covered with the surface material. The material of the surface material covering the sides is not particularly limited and may be metal, resin such as FRP, or other non-combustible surface material. Metal surface materials may be various types of steel plates, similar to metal surface materials. Resin surface materials are not particularly limited, but may be formed from, for example, FRP. The double-sided non-combustible surface material panel 10 is generally a roughly rectangular parallelepiped, and it is preferable to have four sides, but all of the four sides may be covered with the surface material, or only two opposing sides may be covered with the surface material.
[0068] Multiple panels 10 with double-sided fire-resistant surface material may be used in a connected manner. When multiple panels are connected, it is preferable that each double-sided fire-resistant surface material panel 10 be connected to each other by their sides. When connected by their sides, the surface material on the sides of the panels may have irregularities or other features formed on them so that they can be fitted together and connected.
[0069] Panels with double-sided fire-resistant facings are suitable for use, for example, in partitions of buildings to separate areas. Examples of partitions in buildings where panels with double-sided fire-resistant facings are installed include walls, partitions, floors, ceilings, and roofs, with walls and partitions being preferred, and fire-resistant exterior walls and fire-resistant partitions being more preferred. Furthermore, as fire-resistant exterior walls and fire-resistant partitions, they are preferably used as fire-resistant exterior walls and fire-resistant partitions for refrigerator rooms, and in particular, they are preferably used as fire-resistant partitions for refrigerator rooms. As fire-resistant partitions, they may be used as fire-resistant partitions between refrigerator rooms and ambient temperature rooms, or between refrigerator rooms and refrigerator rooms, or between refrigerator rooms and freezer rooms.
[0070] <Manufacturing method for panels with double-sided fire-resistant surface material> The double-sided non-combustible surface panel of the present invention can be manufactured by filling the space between the surface materials with a urethane resin composition, foaming and curing the urethane resin composition to form a polyurethane foam, and then integrating the polyurethane foam with the surface material.
[0071] For example, a laminated panel with non-combustible facings on both sides can be manufactured by supplying a urethane resin composition onto one facing material, arranging the other facing material to cover the top of the supplied urethane resin composition with a predetermined distance between them, and foaming the urethane resin composition to form a polyurethane foam. In this method, panels with non-combustible facing materials on both sides are manufactured continuously. Specifically, in the manufacturing line, a urethane resin composition is discharged from a discharge head provided in the manufacturing line onto one of the conveyed facing materials, while the other facing material is supplied so as to cover the top of the discharged urethane resin composition. Then, the urethane resin composition is foamed and cured between the two facing materials flowing on the manufacturing line to form a polyurethane foam between the two facing materials.
[0072] Alternatively, a mold may be used to manufacture a panel with non-combustible facing material on both sides. Specifically, facing materials are set at predetermined intervals inside a mold such as a press machine, a urethane resin composition is poured into the mold, and the urethane resin composition is foamed and cured between the facing materials to form a polyurethane foam between the two facing materials. Surface materials to cover the sides may also be set inside the mold as appropriate to provide surface materials to cover the sides. The facing materials, polyurethane foams, and laminates of facing materials obtained by the above methods may be used as panels with non-combustible facing materials on both sides, or they may be cut as needed before use.
[0073] Furthermore, the double-sided fire-resistant panel of the present invention may be manufactured by combining, for example, a pre-manufactured core material and a panel material. For example, a panel with a double-sided fire-resistant panel may be made by laminating a panel material onto a pre-manufactured core material. In this case, the core material may be obtained, for example, by foaming and curing a urethane resin composition on any of the above-mentioned layers to form a polyurethane foam, and then processing the polyurethane foam into a desired shape by cutting or other methods. Alternatively, the urethane resin composition may be injected into a mold or the like, foamed and cured inside the mold or the like, and then released from the mold to obtain a core material having a desired shape.
[0074] Furthermore, if a panel with double-sided fire-resistant facing material includes facing material that covers the front and back of the core material, as well as surface material that covers both sides of the opposing core material, a rectangular frame-shaped member composed of a pair of facing material and a pair of surface material that constitutes the sides may be obtained by bending a metal material or joining fire-resistant facing material as appropriate, and a panel with double-sided fire-resistant facing material may be obtained by inserting the core material into the rectangular frame-shaped member. Alternatively, a panel with double-sided fire-resistant facing material may be obtained by fitting a core material between two U-shaped facing materials. [Examples]
[0075] The present invention will be described in more detail below with reference to examples, but the present invention is not limited in any way by these examples.
[0076] The evaluation methods for each example and comparative example are as follows.
[0077] <Calculation of major, medium, and minor diameters, volume, and equivalent spherical diameter of the filler> A sample containing fillers was imaged using an X-ray CT scanner. Subsequently, the filler region was extracted from the captured images using image analysis, and the major, medium, and minor diameters, volume, and equivalent spherical diameter of the filler were calculated from the extracted filler region. Image acquisition and image analysis are performed, for example, as follows.
[0078] [Preparation of measurement sample] Place 1.0 mg of weighed filler onto a PET sheet, add 120 mg of UV resin, and mix with a rubber spatula for about 10 seconds. After mixing, cure using a UV light. At this time, it is acceptable for air bubbles to be included in the sample. After curing, cut the sample to 1.4 mm x 10 mm x 2 mm. The UV resin used was UV KNOT SENSE from LOON OUTDOORS.
[0079] [X-ray CT device] 3DX-ray microscope (high-resolution 3DX-ray microscope nano3DX, manufactured by Rigaku Corporation) [X-ray CT measurement conditions] X-ray target: Cu Lens: L0270 (0.53μm / pixel) Binning: 2 Exposure time: 16 seconds Number of images: 1000 sample images Shape: 1.4mm x 10mm x 2mm
[0080] [Image Analysis] Images obtained from an X-ray CT scanner were analyzed using the image analysis software Avizo 3D Pro 2023.1.1 (manufactured by Thermo Fisher Scientific) following the procedure below. (i) Image cropping: Apply "Crop Editor" to the acquired image and crop it so that the measurement sample occupies the entire image. The cropped image size is, for example, x=1150, y=1050, z=1200. (ii) Bubble region extraction: Apply "Interactive Thresholding" to the image from (i) and adjust the threshold so that bubble regions are extracted. Then, apply "Closing", "Fill Holes", "Remove Small Spots", and "Dilation" to remove noise from the extracted region. The conditions for each analysis module may be as follows, for example: Interactive Thresholding Intensity Range: 0-60 Closing Size: 1 All other conditions will be left at their default values. · Fill Holes Interpretation: XY planes All other conditions will be left at their default values. Remove Small Spots Interpretation: 3D Size: 10000 Dilation Size: 5 All other conditions will be left at their default values. (iii) Filler region extraction - 1: Apply "Interactive Thresholding" to the image from (i) and adjust the threshold so that the filler region is extracted. The conditions for each analysis module may be as follows, for example: Interactive Thresholding Intensity Range: 105-255 (iv) Filler region extraction-2: Apply "AND NOT Image" to the image from (iii) to extract the filler region by excluding the extracted region from (ii) from the extracted region from (iii). Then, apply "Remove Small Spots" and "Border Kill" to remove noise and filler adjacent to the edges of the image. The conditions for each analysis module may be as follows, for example: Remove Small Spots Interpretation: 3D Size: 9 Border Kill This will be the initial value. (v) Feature quantity analysis of filler regions: "Label Analysis" was applied to the image of (iv) to analyze the feature quantities (major diameter, medium diameter, minor diameter, volume) of each filler region. The actual size values were calculated from the obtained feature quantities using the following formula. Furthermore, the average value of each feature quantity of the calculated actual size was calculated by dividing the sum of the feature quantities by the number of analyzed filler regions. ·Actual size length (major diameter, medium diameter, minor diameter) Actual size length (μm) = Length (pixel) × Resolution (μm / pixel) ·Actual size volume Actual size volume (μm 3 ) = Volume (voxel) × Resolution (μm 3 / voxel) The obtained average values of the actual size lengths (major diameter, medium diameter, minor diameter) of the filler and the average value of the actual size volume were substituted into the following formula (1). The results are shown in Tables 1 and 2. (Major diameter × Medium diameter ÷ Minor diameter) ÷ Volume ··· (1) (vi) Calculation of equivalent spherical diameter of filler regions: The equivalent spherical diameter was calculated from the actual size volume analyzed in (v) using the following formula (2). Furthermore, the average value of the equivalent spherical diameters was calculated by dividing the sum of the calculated equivalent spherical diameters by the number of analyzed filler regions. The average values of the equivalent spherical diameters are shown in Tables 1 and 2. Equivalent spherical diameter (μm) = 2 × {Volume (μm 3 ) × 3 / 4 / Pi} 1 / 3 (2)
[0081] [Overall Density] The mass and volume of the entire core material (polyurethane foam) produced in each Example and Comparative Example were measured, and the overall density was calculated from the measured mass and volume.
[0082] [Fire Resistance Performance] A sample of 99 mm × 99 mm × 25 mm was cut out from the central portion of the core material obtained in each Example and Comparative Example, and 4 points of length in the width direction and 4 points of length in the thickness direction were respectively measured. Specifically, the measurement was performed as follows. A 0.5 mm thick steel plate was placed on both the heated and unheated sides of the above sample to create a sample for cone calorimeter testing. Subsequently, the sample was subjected to a radiant heat intensity test of 50 kW / m² in accordance with the ISO-5660 test method. 2 After heating for 15 minutes, all steel materials were removed from the sample, and the length of four points in the width direction and four points in the thickness direction of the polyurethane foam were measured, and the average length was calculated for each direction. Next, the rates of change of the length in the width direction and the length in the thickness direction were determined based on the following equations (A) and (B). • Percentage change in width (%) = Average width after the above test (mm) / Width before the above test (mm) × 100 ... (A) • Percentage change in length in the thickness direction (%) = Average length in the thickness direction after the above test (mm) / Length in the thickness direction before the above test (mm) × 100 ... (B)
[0083] Furthermore, the fire resistance performance was evaluated based on the following evaluation criteria. ○: Both the rate of change in length in the width direction and the rate of change in length in the thickness direction were 10% or less. ×: At least one of the change rates of length in the width direction and the change rate of length in the thickness direction exceeded 10%.
[0084] [Thermal conductivity] Samples measuring 200 mm x 200 mm with a thickness of 25 mm were cut from the central portion of the core material obtained in each example and comparative example, and their thermal conductivity was measured using a thermal conductivity measuring device (product name "HC-074") manufactured by Eiko Seiki Co., Ltd. Based on the measured thermal conductivity, the thermal insulation performance was evaluated according to the following evaluation criteria. 〇: 0.035W / (m·K) or less ×: Greater than 0.035 W / (m·K)
[0085] [Residue retention] When the residue removed from the electric furnace was picked up by pinching it from both sides with one hand, it was evaluated as follows: "A" if it could be lifted with almost no change in shape, "B" if there was some damage but the change in shape was not significant, "C" if the shape remained but it crumbled when pinched with the hand and could not be lifted, and "D" if the shape itself was not preserved.
[0086] [Volume retention rate] The polyurethane foam, with the 20mm skin layer removed, was cut to dimensions of 50mm x 50mm and 20mm thick, placed on a thin steel plate, and placed in an electric furnace heated to 600°C. After the polyurethane foam was placed in the furnace, the temperature of the electric furnace was increased from 600°C to 800°C over 6 minutes, and maintained at 800°C for 14 minutes. The residue after heating was then removed from the electric furnace. The volume retention rate was determined by calculating the ratio of the external volume of the residue after removal from the electric furnace to the volume of the polyurethane foam before being placed in the electric furnace. Products with a volume retention rate of over 80% were evaluated as "A", those with a volume retention rate of over 50% and 80% or less were evaluated as "B", those with a volume retention rate of over 20% and 50% or less were evaluated as "C", and those with a volume retention rate of 20% or less were evaluated as "D".
[0087] The components used in each example and comparative example are as follows: (Polyol compounds) Polyester polyol, manufactured by WOOJO HIGHTECH, product name: WJESOPOL6201, hydroxyl value = 235 mgKOH / g Polyether polyol, manufactured by Mitsui Chemicals, Inc., product name: NFS-24, hydroxyl value = 235 mg KOH / g (Polyisocyanate compounds) Polymeric MDI: Manufactured by Tosoh Corporation, Product name: Millionate MR-200 (Foam stabilizer) Silicone-based foam stabilizer: Manufactured by Dow Toray, Product name: SH-193
[0088] (catalyst) Resinization catalyst: Kao Corporation, product name: Kaolizer No. 120, 1-isobutyl-2-methylimidazole (concentration 98-100% by mass) Trimerization catalyst: Manufactured by Toei Chemical Co., Ltd., Product name: Potassium hexoate, potassium 2-ethylhexanoate (Concentration: 75% by mass)
[0089] (Foaming agent) Hydrofluoroolefin (HFO): trans-1-chloro-3,3,3-trifluoropropene (manufactured by Honeywell Japan, product name: Solstice LBA) water (Plasticizer) Phosphate ester (1): Manufactured by Daihachi Chemical Co., Ltd., Product name: TMCPP, Tris(β-chloropropyl) phosphate Phosphate ester (2): Manufactured by Daihachi Chemical Co., Ltd., Product name: CR-504L, Polyoxyalkylene bis-dichloroalkyl phosphate
[0090] (Filler) Mica (1): Manufactured by Yamaguchi Mica Co., Ltd., Product name: Y-1800 Mica (2): Manufactured by Yamaguchi Mica Co., Ltd., Product name: TM-10 Mica (3): Manufactured by Osaka Mica Co., Ltd., Product name: H-2000 Mica (4): Manufactured by Repco, Product name: M-60 Talc: Manufactured by Yamaguchi Mica Co., Ltd., Product name: CT-30 Wollastonite: Manufactured by Kansai Matec Co., Ltd., Product name: KGP-H40 Kaolin: Manufactured by Tomoe Industrial Co., Ltd., Product name: DG80X Barium sulfate: Manufactured by Nishifuka Kako Co., Ltd., product name: D-0.6
[0091] [Examples 1-14, Comparative Examples 1-3] A polyol premix liquid (polyol liquid agent) was prepared by pre-mixing raw materials other than the polyisocyanate compound according to the formulations shown in Tables 1 and 2. A mold with heat-retaining metal press plates on the top and bottom was also prepared. After heating the metal press plates to 60°C, the urethane resin composition obtained by mixing the polyisocyanate compound with the polyol liquid agent was filled between the metal press plates and foamed and cured in the mold for 30 minutes to obtain a core material made of polyurethane foam. The density, fire resistance, and thermal conductivity of the core materials produced in each example and comparative example were evaluated. As described above, the fire resistance was evaluated after placing a steel material on the surface of the core material. The results are shown in Tables 1 and 2.
[0092] [Table 1]
[0093] [Table 2] *In Tables 1 and 2, the catalyst content is the amount in the final product.
[0094] As is clear from the above examples, the core material produced in the examples was made from a urethane resin composition containing a filler having a predetermined shape, and therefore exhibited excellent fire resistance and heat insulation properties. In contrast, the core material prepared in the comparative example was made from a urethane resin composition that did not contain fillers of a predetermined shape, and therefore could not obtain excellent fire resistance. [Explanation of Symbols]
[0095] 10 Panels with double-sided fire-resistant surface material 11,13 Core material (polyurethane foam) 12,14 Inorganic core material 20,21 Non-combustible surface material
Claims
1. A panel with a double-sided non-combustible surface material having a core material formed from a urethane resin composition containing a polyol compound, a polyisocyanate compound, a filler, a foaming agent, and a catalyst, A panel with a double-sided non-combustible surface material, wherein the parameters obtained by substituting the major diameter, medium diameter, minor diameter, and volume of the filler, obtained by image analysis of an image of the filler taken with an X-ray CT scanner, into the following formula (1) are greater than 0.
10. (Major diameter × Medium diameter ÷ Minor diameter) ÷ Volume ... (1)
2. The panel with a double-sided non-combustible surface material according to claim 1, wherein the catalyst includes a trimerizing catalyst.
3. The density of the core material formed from the aforementioned urethane resin composition is 30 to 180 kg / m³. 3 A panel with a double-sided non-combustible surface material as described in claim 1 or 2.
4. The panel with double-sided non-combustible surface material according to claim 1 or 2, wherein the thermal conductivity of the core material formed from the urethane resin composition is 0.035 W / (m·K) or less.
5. The panel with double-sided non-combustible surface material according to claim 1 or 2, wherein the thickness of the core material formed from the urethane resin composition is 50 to 300 mm.
Citation Information
Patent Citations
Fireproofing panel
JP1994123141A
Sandwich panel
JP2021088923A